Emerging Role of Primary Cilia as Mechanosensors in Osteocytes - Nguyen, An M. (2012)
The primary cilium is a solitary, immotile microtubule-based extension present on nearly every mammalian cell. This organelle has established mechanosensory roles in several contexts including kidney, liver, and the embryonic node. Mechanical load deflects the cilium, triggering biochemical responses. Defects in cilium function have been associated with numerous human diseases. Recent research has implicated the primary cilium as a mechanosensor in bone. In this review, we discuss the cilium, the growing evidence for its mechanosensory role in bone, and areas of future study. This article is part of a Special Issue entitled “Osteocytes”.